1976
DOI: 10.1029/jb081i026p04909
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical resistivity variations along stressed strike-slip faults

Abstract: A simple model of a strike-slip fault is analyzed to see if observable resistivity variations would be produced by strain' accumulation. Fault displacement is found to produce only pure shear loading.Estimates of the effect of this stress system on rock resistivity are made by using existing resistivity data measured during isotropic and triaxial loading. For a model of the San Andreas fault, 50 cm of fault displacement are found to produce apparent resistivity variations of about 1%. The model considered requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this context, one of the most challenging research problems still debated in the geoscience community is the study of subsurface resistivity changes before, during, and after earthquakes. In a seminal paper, Fitterman [13] introduced the theoretical basis underlying possible variations in the spatio-temporal patterns of earth resistivity close to active fault systems. Rikitake [14] and Gokhberg et al [15] considered this geophysical parameter as a possible earthquake precursor.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, one of the most challenging research problems still debated in the geoscience community is the study of subsurface resistivity changes before, during, and after earthquakes. In a seminal paper, Fitterman [13] introduced the theoretical basis underlying possible variations in the spatio-temporal patterns of earth resistivity close to active fault systems. Rikitake [14] and Gokhberg et al [15] considered this geophysical parameter as a possible earthquake precursor.…”
Section: Introductionmentioning
confidence: 99%
“…The striking changes in electrical resistivity and its anisotropy were widely observed before earthquake, mine earthquake, volcanic activities, and geologic motions [1][2][3][4][5][6][7][8][9][10][11][12]. In order to address the change characteristics of resistivity and its anisotropy, many investigators conducted a plenty of experiments on rock samples under compression and during fracture, shear, and frictional sliding in lab [13][14][15][16][17][18][19][20][21][22][23][24][25] and theoretic studies [26][27][28][29][30]. Experimental results reported by Brace et al [13] and Brace and Orange [14][15][16] in lab showed that striking changes in electrical resistivity were observed for a variety of igneous and sedimentary crystalline rocks when water-saturated crystalline rocks were stressed to fracture.…”
Section: Introductionmentioning
confidence: 99%